2015
DOI: 10.1179/1362171815y.0000000021
|View full text |Cite
|
Sign up to set email alerts
|

Improved weld macrosection, microstructure and mechanical properties of 2024Al-T4 butt joints in ultrasonic vibration enhanced friction stir welding

Abstract: Ultrasonic vibration enhanced friction stir welding (UVeFSW) is a new variant of friction stir welding (FSW) in which a sonotrode transmits ultrasonic energy directly into the localised area of the workpiece near and ahead of the rotating tool. This study investigated the influence of ultrasonic vibration on the formation, microstructure and mechanical properties of butt welded 2024Al-T4 joints, and attempted to unveil the underlying mechanism of UVeFSW by experimental methods. Morphology inspection, X-ray det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(43 citation statements)
references
References 22 publications
1
36
0
Order By: Relevance
“…The overall result of these two effects may increase the heat input slightly. UAFSW expanded the plastically deformed region [24] and improved the material ow [25], thus it improved lap shear force and hardness of the joints [25]. UAFSW also suppressed the formation of voids and tunnel defects [24,26].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The overall result of these two effects may increase the heat input slightly. UAFSW expanded the plastically deformed region [24] and improved the material ow [25], thus it improved lap shear force and hardness of the joints [25]. UAFSW also suppressed the formation of voids and tunnel defects [24,26].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Liu et al 95 exhibited an improved microstructure of butt weld joints created using a friction welding process boosted with ultrasonic vibrations. 2024Al-T4 butt joints were experimentally examined along with metallographic/X-ray visualizations which revealed better microstructure and grains formation.…”
Section: Welding With Vibration Assistancementioning
confidence: 99%
“…Blaha and Langenecker found that the use of ultrasonic vibration could reduce the yield stress and promote the plastic deformation of the metals [ 150 ], which was similar to heat softening. While the heat energy is uniformly absorbed by the metals, the ultrasonic energy can only be absorbed by the crystal defects in the metal [ 151 ]. Moreover, the plastic deformation of metals only depends on dislocation movement.…”
Section: Low-heat-input Weldingmentioning
confidence: 99%